Craniofacial resection due to esthesioneuroblastoma: A case report - Muhlis Bal; Yavuz Uyar; Güven Yıldırım; Ayşe Hatipoğlu; Gürcan Sünnetçi; Celal İplikçioğlu (Turkish Archives of Otorhinolaryngology, 2011)

(untitled)
Esthesioneuroblastoma is a rare, malignant tumor originating from the olfactory neuroepithelium in the nasal cavity. This tumor has been called olfactory neuroblastoma, olfactory esthesioneuroblastoma and neuroendocrine carcinoma in the literatüre. Esthesioneuroblastoma is the term used most commonly. Tumor may invade the nasal cavity paranasal sinuses, the orbit and the cranial cavity. An esthesioneuroblastoma which was operated because of recurrence has been presented with clinical, radiological and histopathological aspects by literature.